Incomptines C and D, Two Heliangolides from Decachaeta incompta and Their Antiprotozoal Activity - Bautista, Elihú; Calzada, Fernando; Yepez-Mulia, Lilian; Chavez-Soto, Marco; Ortega, Alfredo (Planta Medica, 2012)
Two new heliangolides, incomptines C (3) and D (4), were isolated from the leaves of Decachaeta incompta. The structures were established by spectroscopic methods and confirmed by X-ray crystallography. The antiprotozoal activity of incomptines C and D was evaluated. Additionally, the chromatographic profile of the leaves and roots extracts were compared to identify incomptines A–D (1–4) in each extract.
Keywords: Asteraceae; Decachaeta incompta; Giardia lamblia; Entamoeba histolytica; heliangolides; antiprotozoal activity